Detrusor Underactivity in Men with Bladder Outlet Obstruction - Hsiang-Ying Lee; Chien-Sheng Wang; Yung-Shun Juan (Biomedicines, 2022)
Detrusor underactivity (DU) and bladder outlet obstruction (BOO) are both common troublesome causes of lower urinary tract symptoms (LUTS) and often impact on quality of life simultaneously in men. This article aims to focus on DU with BOO in male patients. Methods: Original articles concerning DU with BOO were identified through literature research from PubMed and EMBASE database. We selected 38 articles in our review, including those concerning pathophysiology, evaluation, treatment and predictors for a successful BOO surgery for DU. Results: DU from BOO can result from several pathophysiological mechanisms. Although urodynamic study (UDS) is considered as a precise method to diagnose DU and BOO, there are some previous studies which proposed a non-invasive method to identify DU related to BOO. The treatment goal of DU is restoring bladder contractility using medication or surgery. Releasing outlet obstruction and resistance is the main strategy to restore bladder contractility when medication to directly increase bladder contractility has had limited efficacy. Conclusions: DU from BOO is poorly understood and is largely under-researched. The etiology and pathophysiology still need to be evaluated. Effective and safe medication to restore bladder contractility is also lacking. It remains valuable to perform further research to reveal the unknown aspects of DU.